EMPLOYEE TRAINING AND DEVELOPMENT, WORK ENVIRONMENT AND LEADERSHIP ON EMPLOYEE COMPETENCE AND PERFORMANCE IN GOVERNMENT OF BAUBAU CITY, SULAWESI TENGGARA - Sulhan Manaf (SEAN Institute, 2023)
Organizations aspire to succeed through differentiated programs, services, capabilities and products. However, these elements need to be envisioned, developed, implemented and maintained by well-trained individuals. The purpose of this research is to see how the training and development of employees. Work environment and leadership affect employee competence and performance. This study uses descriptive qualitative research. Interview techniques are used in the data collection process to collect information about how employee training and development, work environment and leadership factors affect employee competence and performance. The results of the research analysis show that the training and development of employee performance in the Baubau city government of the Southeast Sulawesi Province is through formal courses and programs, assessments. The work environment has an influence on employee competence and performance by dividing it into 2 indicators, namely by looking at the physical environment and non-physical environment. leadership carried out. Leadership in improving employee competence and performance is by consistently providing training programs to fill skill gaps that employees do not have. the results of interviews conducted with informants showed that every employee must always be given direction in every procedure, job description, and workload. Employees will understand what will be done and have the initiative to generate fresh new ideas to improve their performance.